2018
DOI: 10.1039/c8dt03254h
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent liquid crystalline hybrid materials by embedding octahedral molybdenum cluster anions with soft organic shells derived from tribenzo[18]crown-6

Abstract: Crown ethers and their derivatives are versatile building blocks for the design of supramolecular materials. They can be functionalized at will and are well known for their abilities to complex with alkali cations. Here, we show that emissive lanthanide free hybrid materials can be generated by using such building blocks. The organic tribenzo[18]crown-6 central core was functionalized via six-fold Suzuki cross-coupling as a key reaction with three o-terphenyl units which could be converted into their correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…27,38,42 In addition, previous work on tribenzo [18]crown-6 derivatives revealed that the tribenzo [18]crown-6 triphenylenes decomposed upon attempted complexation with the cluster salts, whereas the corresponding o-terphenyls formed stable clustomesogens. 28 Sodium salts of metal clusters were synthesized in solution starting from (H 3 O) 2 Mo 6 Cl 14 •7H 2 O or Mo 6 Br 12 as described in the Experimental Section. The identity and purity of the cluster salts were assessed by X-ray diffraction (XRD), powder diffraction, and energy-dispersive spectroscopy (EDS) analyses.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…27,38,42 In addition, previous work on tribenzo [18]crown-6 derivatives revealed that the tribenzo [18]crown-6 triphenylenes decomposed upon attempted complexation with the cluster salts, whereas the corresponding o-terphenyls formed stable clustomesogens. 28 Sodium salts of metal clusters were synthesized in solution starting from (H 3 O) 2 Mo 6 Cl 14 •7H 2 O or Mo 6 Br 12 as described in the Experimental Section. The identity and purity of the cluster salts were assessed by X-ray diffraction (XRD), powder diffraction, and energy-dispersive spectroscopy (EDS) analyses.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As defined by Cotton et al cluster compounds are aggregates of finite dimensions of metal atoms connected to each other by metal–metal bonding. Transition metal cluster compounds are widely used for their luminescence or UV–NIR absorption properties. In this work, the true nanoscale aspect (∼1 nm) of these compounds is used to form nanostructured molybdenum nitrides. Several molybdenum cluster compounds are treated at different temperatures under a fixed ammonia flow of 30L/h.…”
Section: Resultsmentioning
confidence: 99%
“…• RESULTS AND DISCUSSION Choice of the precursor As defined by Cotton et al 35 cluster compounds are aggregates of finite dimensions of metal atoms connected to each other by metal-metal bonding. Transition metal cluster compounds are widely used for their luminescence or UV-NIR absorption properties [36][37][38][39][40] . In this work, the true nanoscale aspect (≈1 nm) of these compounds is used in order to form nanostructured molybdenum nitrides.…”
Section: Thermogravimetric Analyses (Tga-ms)mentioning
confidence: 99%
“…In addition to the two previous approaches, Molard and coworkers developed another strategy with hexametallic clusters which consisted in trapping the alkali counter cations, especially K + and Cs + , within functionalized 15C5 or 18C6 crown ethers (see Figure 10). [91,92] Following this idea, they succeeded to design columnar hexagonal arrangements mainly due to discotic-like complex formed between the crown ethers and the alkali, while the metallic clusters, well known for their strong luminescence properties, were localized between the columns (see Figure 11). Even if this family of clusters does not formally belong to POM's family, this strategy constitutes a very interesting perspective for developing new POM-based ionic liquid crystals with new arrangements.…”
Section: -3 An Original Promising Approach By Encapsulating Akali Counter-cationsmentioning
confidence: 99%
“…Figure 10. Representation of 15C5 and 18C6 crown ethers derivatives used by Molard and coworkers to coordinate K + and Cs + counter cations paired with hexametallic clusters [Mo 6 X 14 ] 2-(X = Cl, Br, I) and [Mo 6 I 8 (C 2 F 5 COO) 6 ] 2- [91,92]. …”
mentioning
confidence: 99%